META-ANALYSIS OF EFFECT SIZE: THE EFFECT OF USING ETHNOSCIENCE-BASED SCIENCE AND PHYSICS TEACHING MATERIALS ON STUDENTS' SCIENCE LITERACY - Tusa'diah, Halimah; ,, Asrizal; ,, Festiyed (Journal of Learning and Technology in Physics, 2024)
This study examines the effect of teaching materials in ethnoscience-based science and physics learning on students' scientific literacy, determined through Effect Size (ES). This study uses a descriptive meta-analysis study method. Research data were obtained from 20 journals on the effect of ethnoscience-based physics and science teaching materials on students' scientific literacy. The study is based on three categories, namely the level of education, types of teaching materials and scientific literacy skills. The results showed that; first, the effect of teaching materials in ethnoscience-based science and physics learning on scientific literacy based on education level has a positive effect on all levels of education starting from elementary, junior high, high school and college students. Second, based on the type of teaching materials used, namely modules, worksheets, videos, teaching materials, reading books and comics, they have a high effect. Third, based on the scientific literacy of students, it shows that the use of ethnoscience-based science and physics teaching materials is effective in increasing students' scientific literacy.Keywords: Meta Analysis, Teaching Materials, scientific literacy